Science Teachers’ Motivation for Teaching in the Light of their Educational Vision: Teaching as a Career vs. Teaching as a Job - Abu Al- Haijaa, Ghada Saleh; Bani Khalaf, Mahmoud Hassan (Dirasat: Educational Sciences, 2023)
Objectives: The study aims to investigate science teachers’ educational vision (between teaching as a career and teaching as a job) and its connection to their motivation for teaching. Methods: The study uses convenient sampling. The sample consists of (234) male and female science teachers in the Directorate of Education of Qasabah Irbid District. To achieve the objectives of the study, the two researchers designed a questionnaire to determine science teachers’ educational vision. The questionnaire consists of (40) items distributed over two main domains, namely: (teaching as a career) and (teaching as a job). The researchers also developed a motivation-for-teaching scale consisting of (25) items. The validity and reliability of the two research tools were verified. Results: The results show that science teachers’ educational vision (between teaching as a career and teaching as a job) is associated with a statistically significant relationship with their motivation for teaching. It also shows that the motivation for teaching differs according to the educational vision in favor of science teachers whose educational vision perceives teaching as a career. Finally, the study shows that the level of motivation of science teachers is very high. Conclusion: The research highlights the necessity for strengthening and consolidating the concept of teaching as a career among science teachers.